2012
DOI: 10.5455/cap.20120417
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Postpartum Mental Status and Breastfeeding

Abstract: ÖZETGünümüzde anne sütü ve emzirmenin önemi kadar önemli olan bir başka konu da doğum sonrası annenin ruh sağlığıdır. Annenin bebeğine sağlıklı bir şekilde bakabilmesi ve uzun dönem emzirebilmesi için öncelikle kendi beden ve ruh sağlığının yerinde olması gerekir. Anne ruh sağlığının kötü olması, bebeğin iyi beslenememesi ve fiziksel sağlığında bozulmalarla sonuçlanmakta-dır. Depresif annelerin emzirme konusunda daha fazla kaygılandıkları, sütleri-nin besleyiciliği ve yeterliliği konusunda olumsuz düşüncelere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Rising beta‐endorphin levels with physical contact and breastfeeding strengthen the interaction between the mother and the infant within the first hours after birth. The secretion of beta‐endorphins raises the pain threshold and reduces or eliminates the feeling of pain (Annagür & Annagür, 2012; Kesebir & Aksoy, 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rising beta‐endorphin levels with physical contact and breastfeeding strengthen the interaction between the mother and the infant within the first hours after birth. The secretion of beta‐endorphins raises the pain threshold and reduces or eliminates the feeling of pain (Annagür & Annagür, 2012; Kesebir & Aksoy, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Rising beta-endorphin levels with physical contact and breastfeeding strengthen the interaction between the mother and the infant within the first hours after birth. The secretion of beta-endorphins raises the pain threshold and reduces or eliminates the feeling of pain (Annagür & Annagür, 2012;Kesebir & Aksoy, 2010. Despite copious studies regarding the effects of SSC on maternal and neonatal health, few studies have evaluated its effects on pain levels and hemorrhage in the early postpartum period, and those that do exist have presented conflicting results (Almutairi, 2017;Saxton et al, 2015;Sharma, 2016). Vittner et al (2018) and Cong et al (2015) reported that SSC initiatives increase the oxytocin levels of mothers.…”
mentioning
confidence: 99%